Cytology of fungal pathogens and plant-host interactions - Howard, R.J.
Imaging plays a unique role in fungal cell biology and phytopathology by allowing for the documentation of molecular structure in individual fixed and living cells. Advances in fluorescence laser techniques, including confocal and multiphoton microscopy, are opening new avenues for cellular exploration. These techniques hold tremendous potential for studies of host-pathogen interactions including the use of genetically encoded markers such as green fluorescent protein, in situ hybridization and fluorescence resonance energy transfer.
Keywords: CRYO-FIXATION; CYTOCHEMISTRY; FLUORESCENCE MICROSCOPY; FUNGI; GREEN FLUORESCENT PROTEIN; IMAGING; PLANT DISEASE